THE IMPORTANCE OF IMPLEMENTATION OF MULTIMEDIA TECHNOLOGY IN TEACHING - Xodjimuratova, Malika Valiyevna; Umarxo‘jayeva, Hilola Sirojiddinovna (Innovative Development in Educational Activities, 2023)
The article describes the significance of utilizing multimedia technology in teaching. It deals with some problems in the process of teaching and assessing. Moreover, article includes the role of Web applications in enhancing students’ motivation. Nowadays, information communication technology (ICT) has become one of the crucial part of the education that is always emphasized, especially by foreign language pedagogy scholars. The aim of the paper is to introduce the innovative method of assessment using web application. Furthermore, work includes the best examples of Web applications, which is crucial for efficient teaching and assessing.